Paradigm in Higher Education in COLOMBIA (Docentes 2.0 Journal, 2015)
Colombia is a unitary republic of America located in the northwestern region of South America, constituted in a social and democratic state of law whose form of government is presidential. Its capital is Bogota. Although Latin America is an ambiguous region with many peculiarities in education, the case of Colombia is interesting to analyze given the particular way in which its higher education has evolved. A constant interest in forming critical bodies and constituting high-level educational institutions has been the constant in the construction of an adequate support that allows to respond to the university reality as well as to direct the State to a timely and efficient decision making.
Keywords: Paradigm; Higher Education; COLOMBIA